Application Design of Optical Network Defect Tracking based on Location-Based Service - Sutrisno, Eko Setyo; Hantoro, Kusdarnowo (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2020)
To maintain good service quality, network maintenance is needed. Device maintenance must be carried out as quickly and accurately if supported by an application device that can find the right location as fast as possible. Maintenance devises related to defective optical network cables, optical distribution point (ODP) panel, and ODC (Optical Distribution Cabinet) panel, to FTM (Fiber Termination Management) room. Through the three existing locations, maintenance technicians often  difficulties to find the exact location of the ODC and to find out the status of the ports that are in the ODC. By utilizing features on mobile devices. LBS communicates from two-way interactions and can combine three technologies: Geographic Information System, Internet Service, and Mobile Device